Online reservation system for IranAir / Laleh Rahimi - Rahimi, Laleh (2009)
The Major problem of IranAir system is that it doesn't have an online international flight bookings. The current system of IranAir includes an online booking system for internal flights only. This work presents the performance to design and develop a new website for IranAir and adding an event calendar to the webpage. Rapid application development is a software development process, which involves iterative development and the construction of prototypes. By using this methodology some advantages may be gained including: increased quality of the application because the system design involves the customers and hence it should comply with their needs, the system also will have fewer defects and errors owing to the use of CASE tools and using an integrated development environment the time of developing the system is minimized. By going through some existing airlines online booking systems it has been concluded that none of them are having an event calendar while the passenger is booking the ticket. The idea of showing the events while booking a ticket is to instantly let the customer know about the important events and holidays in destination country at the date of travel. The system which has been developed includes a prototype of a booking system with an event calendar using AJAX technology. The customers can register accounts so that they don't need to fill up all the forms every time they book a flight and they may view all their transactions history. An administration panel has also been developed so that the system administrator is able to easily track and make any changes to the system's database.